Plan estratégico y su relación con el mejoramiento de los servicios educativos de la Unidad Educativa Réplica Nicolás Infante Díaz cantón Quevedo período 2015-2019 - Coello Bravo, Evelyn Lorena (2015)
The Replica Education Unit Nicolas Diaz Infant Quevedo Canton, is one of the units of the millennium that the government has implemented, the purpose of these new units is to provide a quality educational service, as the globalized world is advancing education opens new demanding borders and implement policies to address educational change, for all the above the following research entitled STRATEGIC PLAN AND ITS RELATIONSHIP WITH THE IMPROVEMENT OF EDUCATIONAL SERVICES UNIT OF EDUCATIONAL REPLICA "NICOLAS DIAZ INFANTE" presents 2015-2019.through the period and a strategic plan to know how it relates to and influences the improvement of educational services designed, a SWOT analysis was performed to determine the current status of the institution, and the design of the organizational structure of the entity is held stipulating the organization of the information collected to determine the background, history, mission, vision, corporate objectives, policies and values determined all possible strategies to mean a change of continuous improvement in the quality of services. To do this four operational plans, models which are based on the strategic objectives which are mentioned developed: Introduce to the school community the identity of the institution, promote classroom use of virtual spaces to bring teachers and students to the technology and develop skills for use, encourage more efficient use of the installed capacity of the educational unit, support programs that combine periods of stays and student internships in companies and institutions. All this aims to provide quality service and warmth for all.